The Arab uprisings explained : new contentious politics in the Middle East - Lynch, Marc (Columbia studies in Middle East politics., 2014)
Why did Tunisian protests following the self-immolation of Mohammed Bouazizi lead to a massive wave of uprisings across the entire Arab world? Who participated in those protests, and what did they hope to achieve? Why did some leaders fall in the face of popular mobilization while others found ways to survive? And what have been the lasting results of the contentious politics of 2011 and 2012? The Arab uprisings pose stark challenges to the political science of the Middle East, which for decades had focused upon the resilience of entrenched authoritarianism, the relative weakness of civil.